Parade of the Yukon Order of Pioneers for the July 4th celebration, Nome, Alaska, 1901. - Hegg, Eric A., 1867-1948 (1901)
Caption on image: "Y.O.O.P. Nome July 4th 1901" Original image in Hegg Album 5, page 29.